The Role of Sand and Stone Mining to Increase Family Income in Progo Catchment - Su Ritohardoyo (Forum Geografi, 2003)
The conzequence low income of the farmer household in agricultural sector is the increase in their activities as miner of sand and stone. It means for increasing of their household income. However, how important mining role on the increasing of household income has to be studied in deeply. The factual problem is the base for research aims, with the spesific stress on studying socio-economic characteristic of sand and stone miner, and the contribution of the mining income to household income. This research was carried out in Progo catchment area, Yogyakarta Special Region. Survey method was employed by data collecting from respondents. The respondents are head of households (HH) working as sand and stone miner. Sampling technique was proportionally simple random sampling in which 120 HH was taken as respondents sample. They were representatives of upper part, middle part, and lower part of Progo catchments area. Data on socio-economic structure of the household and household income were collected by mean of structured interview. Data analysis was performed through descriptive technique in which frequencies and cross tabulation varians statistic, and multiple regression analysis were mostly used. The research shows that there are relatively similarities on socio-economic characteristic of sand and stone miners, between at lower part, middle part with upper part of Progo catchments area. This existing of sand and stone mining employs about 70% labours are local miners and 30% labours came from out of the area. Landless farmers who land own less than 500 m2 characterize them. The most of them are male, withlow formal education, and as small family (4 people evey HH). Some of them have been as sand and stone miners for more than 4 years. Generally, they work less than 8 hours for mining every day. This research is also finding that the income of the sand and stone miners are seasonal. The averages of mining income on dry season (Rp 571,880 per month) are higher than on wet season (Rp 365,620 per month). The most important factor affecting income in this activity is the working hours spent. In average, the miner’s monthly income is Rp 468,760 is much higher than minimum level of basic need in Yogyakarta Special Region (Rp 328,750 per month). It means that sand and stone miner as a second occupation besides as a farmer increases household income be capable to satisfy the need of household economy. In general, it can be concluded that the activity has an important role on the increasing of household income.